Pengaruh Kemampuan Menghafal Al-Quran Juz 30 Terhadap Hasil Belajar SiswaPada Mata Pelajaran PAI - Fauziah, Hapsah; Auliyani, Salma (STAI Al-Musaddadiyah Garut, 2023)
Learning outcomes represent the skills and knowledge that students acquire after participating in educational activities, making them a crucial component of the educational process. However, the learning outcomes of students in Islamic Religious Education (PAI) have not yet developed satisfactorily, as evidenced by students' challenges in understanding and remembering the material and their lack of preparedness for participating in learning activities. The ability to memorize the Quran, particularly Juz 30, can have a positive impact on students' performance in PAI subjects. Memorizing the Quran is defined as the ability to recall verses of the Quran without referring to the text (mushaf). Additionally, memorizing the Quran can help restore mental balance and stabilize brain function, thereby enhancing students' memory quality and improving their academic performance in PAI subjects. The purpose of this study is to describe: 1) The learning outcomes of eighth-grade students (Class VIII E) at SMP IT Al-Khoiriyyah Karangpawitan Garut; 2) The ability of these students to memorize Juz 30 of the Quran; 3) The impact of the ability to memorize Juz 30 on the learning outcomes in PAI subjects for these students. The research employs a descriptive quantitative method, which involves collecting data or information about the phenomenon under study. The findings indicate that there is a significant impact of memorizing Juz 30 of the Quran on students' learning outcomes in PAI subjects. This is evidenced by the correlation coefficient (r-value) of 0.4144, which falls within the range of 0.40 – 0.599, categorizing it as moderate, with a percentage influence of 17.172%. Therefore, based on statistical analysis, there is a demonstrated influence of the ability to memorize Juz 30 on the learning outcomes in PAI subjects for eighth-grade students at SMP IT Al-Khoiriyyah Karangpawitan Garut. Keywords : Memorizing the Quran Juz 30, Student Learning Outcomes